Dampak Pandemi Covid-19 terhadap Tenaga Kerja di Indonesia - Maya Friska (Jurnal Ekonomi Dan Statistik Indonesia, 2022)
The case of the Covid-19 pandemic was first detected in Indonesia on March 2, 2020 and is still ongoing. The COVID-19 pandemic has had many social and economic impacts. The impact will be very widespread, starting from politics, economy, social, culture, defense, and security, as well as community welfare. This unstable economy also has an effect on labor conditions in Indonesia, such as the rising unemployment rate. This study aims to determine the effect of the pandemic on unemployed or temporarily unemployed workers based on the classification of place of residence, gender, age, last completed education, expertise, and business field. This study uses the August 2021 National Manpower Survey (SAKERNAS) dataset with the enter method binary logistic regression method. The results showed that the classification of residence. Age, last education completed, expertise, and business field affect the temporary unemployed condition due to COVID-19, while the classification of residence, gender, age, and the last education completed affect the unemployment condition due to COVID-19.